Sonographic measurement of kidney size in geriatric patients - (:unkn) unknown (JOHN WILEY & SONS INC, 2003)
Purpose. The aim of this study was to compare the value of absolute and relative renal length (ARL and RRL, respectively) measurements in determining variations in normal kidney size related to sex, body height, and increasing age among patients older than 60 years. Methods. Kidney sizes were prospectively measured sonographically in patients older than age 60 years. Longitudinal renal lengths (ARLs) were measured, and the RRLs were calculated by dividing the ARL by the body height. ARL and RRL measurements were analyzed according to sex, age, and body height. Results. The ARLs and RRLs of the left kidney in 236 patients were significantly greater than those of the right kidney (p < 0.05) in both sexes. The ARLs for both kidneys were also significantly greater in men than they were in women (p < 0.05). In contrast, the RRLs for both kidneys were significantly lower in men than they were in women (p < 0.05). Both left and right ARLs decreased significantly with increasing age regardless of sex (p < 0.01 and p < 0.05, respectively). The same was true for left and right RRLs (p < 0.01 and p < 0.05, respectively). Conclusions. Renal size decreases with increasing age among patients older than 60 years. In our series of geriatric patients, the use of RRLs could not completely eliminate variations related to a subject's height, sex, and age. Therefore, we recommend that the ARL be used for renal measurements in geriatric patients. (C) 2003 Wiley Periodicals, Inc.
Keywords: kidney; size measurement; kidney; normal; geriatrics; ultrasonography; ADULT VOLUNTEERS; RENAL LENGTH; ULTRASOUND; THICKNESS; CHILDREN; AGE